Validated potentiometric method for the determination of sulfacetamide sodium; application to its pharmaceutical formulations and spiked rabbit aqueous humor - Nariman A. El-Ragehy; Maha A. Hegazy; G. AbdElHamid; Samia A. Tawfik (Faculty of Pharmacy, Cairo University, 2018)
Specific, accurate and precise electrochemical method was developed and validated for the determination of sulfacetamide sodium in presence of its co-formulated drug (prednisolone acetate) and its pharmacopoeial impurities. The method was based on fabrication of membrane sensor. The characteristics of electrochemical response were estimated, and the proposed sensor displayed excellent characteristics for the determination of sulfacetamide sodium in bulk powder, laboratory prepared mixtures, dosage forms and in spiked biological fluid (Rabbit aqueous humor). The sensor was constructed through the use of tetradodecylammonium bromide (TDB) as an anion exchanger and 2-nitrophenyl octyl ether (NPOE) as a plasticizer in polyvinyl chloride (PVC) matrix. The performance characteristics, sensitivity and selectivity were evaluated according to IUPAC guidelines. Linearity was achieved over the concentration range of 1 × 10−4.5-1 × 10−2 M with Nernstian slope of 51.086 mV/decade over the pH range of 5-7. The sensor showed a rapid response (10-15 s) and good stability (up to 4 weeks). The obtained results were statistically compared with the official methods and no significant difference was found regarding accuracy and precision. Keywords: Ion selective electrodes, Prednisolone acetate, Rabbit aqueous humor, Sulfacetamide sodium, Tetradodecylammonium bromide